Food restriction during development delays puberty but does not affect adult seasonal reproductive responses to food availability in Siberian hamsters (Phodopus sungorus). Issue 8 (3rd August 2021) - Bailey, Allison M.; Hall, Carlisha A.; Legan, Sandra J.; Demas, Gregory E.
Abstract: Seasonally breeding animals respond to environmental cues to determine optimal conditions for reproduction. Siberian hamsters ( Phodopus sungorus ) primarily rely on photoperiod as a predictive cue of future energy availability. When raised in long‐day photoperiods (>14 h light), supplemental cues such as food availability typically do not trigger the seasonal reproductive response of gonadal regression, which curtails reproduction in unsuitable environments. We investigated whether recognition of food availability as a cue could be altered by a nutritional challenge during development. Specifically, we predicted that hamsters receiving restricted food during development would be sensitized to food restriction (FR) as adults and undergo gonadal regression in response. Male and female hamsters were given either ad libitum (AL) food or FR from weaning until d60. The FR treatment predictably limited growth and delayed puberty in both sexes. For 5 weeks after d60, all hamsters received an AL diet to allow FR hamsters to gain mass equal to AL hamsters. Then, adult hamsters of both juvenile groups received either AL or FR for 6 weeks. Juvenile FR had lasting impacts on adult male body mass and food intake. Adult FR females exhibited decreased estrous cycling and uterine horn mass indiscriminately of juvenile food treatment, but there was little effect on male reproductive measurements. Overall, we observed a delay in puberty in response to postweaning FR, but this delay appeared not to affect seasonal reproductive responses in the long term. These findings increase our understanding of seasonal reproductive responses in a relevant environmental context. Abstract : Research Highlights: Postweaning food restriction delayed puberty in both sexes. Males that were food restricted as juveniles gained more mass as adults. Females showed decreased reproductive function when food restricted as adults regardless of juvenile treatment.